Are medical procedures that induce coughing or involve respiratory suctioning associated with increased generation of aerosols and risk of SARS-CoV-2 infection? A rapid systematic review. (October 2021) - Wilson, J.; Carson, G.; Fitzgerald, S.; Llewelyn, M.J.; Jenkins, D.; Parker, S.; Boies, A.; Thomas, J.; Sutcliffe, K.; Sowden, A.J.; O'Mara-Eves, A.; Stansfield, C.; et al.
Summary: Background: The risk of transmission of SARS-CoV-2 from aerosols generated by medical procedures is a cause for concern. Aim: To evaluate the evidence for aerosol production and transmission of respiratory infection associated with procedures that involve airway suctioning or induce coughing/sneezing. Methods: The review was informed by PRISMA guidelines. Searches were conducted in PubMed for studies published between January 1 st, 2003 and October 6 th, 2020. Included studies examined whether nasogastric tube insertion, lung function tests, nasendoscopy, dysphagia assessment, or suctioning for airway clearance result in aerosol generation or transmission of SARS-CoV-2, SARS-CoV, MERS, or influenza. Risk of bias assessment focused on robustness of measurement, control for confounding, and applicability to clinical practice. Findings: Eighteen primary studies and two systematic reviews were included. Three epidemiological studies found no association between nasogastric tube insertion and acquisition of respiratory infections. One simulation study found low/very low production of aerosols associated with pulmonary lung function tests. Seven simulation studies of endoscopic sinus surgery suggested significant increases in aerosols but findings were inconsistent; two clinical studies found airborne particles associated with the use of microdebriders/drills. Some simulation studies did not use robust measures to detect particles and are difficult to equate to clinical conditions. Conclusion: There was an absence of evidence to suggest that the procedures included in the review were associated with an increased risk of transmission of respiratory infection. In order to better target precautions to mitigate risk, more research is required to determine the characteristics of medical procedures and patients that increase the risk of transmission of SARS-CoV-2.